2010
DOI: 10.1177/155892501000500102
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction of Cotton Treated with Neutralized Vegetable Oil-based Macromolecular Crosslinkers

Abstract: Maleinized soybean oil (MSO) has been investigated as a flexible, macromolecular crosslinker for cotton fabrics. The ability of MSO to penetrate crystalline cellulose and crosslink aligned cellulose chains upon cure has been in question. This study compares the penetration capability of MSO to dimethyloldihydroxyethyleneurea (DMDHEU), which is the commercial standard for durable press finishing and is an efficient cellulose crosslinker. X-ray diffraction was employed to characterize changes in the crystalline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 14 publications
5
38
0
Order By: Relevance
“…7(a)-(d). The SCF displayed a sharp peak at 2Â = 22.5 • , along with other smaller peaks at 2Â = 14.7 • , 2Â = 16.5 • and 2Â = 34.3 • which is characteristics of cellulose I structure (Ford, Mendon, Thames, & Rawlins, 2010). It is important to note that no significant change can be observed in the crystalline form of the SCF after modification by BSA, GO and rGO.…”
Section: Amount Of Go Loaded Onto the Fabricmentioning
confidence: 97%
“…7(a)-(d). The SCF displayed a sharp peak at 2Â = 22.5 • , along with other smaller peaks at 2Â = 14.7 • , 2Â = 16.5 • and 2Â = 34.3 • which is characteristics of cellulose I structure (Ford, Mendon, Thames, & Rawlins, 2010). It is important to note that no significant change can be observed in the crystalline form of the SCF after modification by BSA, GO and rGO.…”
Section: Amount Of Go Loaded Onto the Fabricmentioning
confidence: 97%
“…Figure 3 shows the XRD patterns of the samples, and the crystallinity index (CI) is shown in Table 3. Raw soybean hulls (SH) had a CI of 33% (Table 3), with peaks at 2θ = 20.6 and 34.7º (Figure 3), which are characteristic of native cellulose or cellulose type I (Ford, Mendon, Thames & Rawlins, 2010). Flauzino Neto et al (2013) observed similar characteristics while studying soybean hulls for the production of cellulose nanocrystals, they reported a predominance of the cellulose type I in raw soybean hulls and a CI of 26.3%.…”
mentioning
confidence: 88%
“…Yang et al [13,14] observed that macromonomers are unable to penetrate the microstructure of cellulose as well as small molecules. However, Ford et al [15] observed that NMSO (156 mg KOH/g) penetrated the amorphous domains of cellulose by the study of X-ray diffraction. Ammonia neutralization enhanced the accessibility of reaction sites upon curing [15], and anhydrides are given the opportunity to react with cellulose hydroxyl groups.…”
Section: Ammonium Hydroxide Neutralized Mso Reactionsmentioning
confidence: 99%
“…However, Ford et al [15] observed that NMSO (156 mg KOH/g) penetrated the amorphous domains of cellulose by the study of X-ray diffraction. Ammonia neutralization enhanced the accessibility of reaction sites upon curing [15], and anhydrides are given the opportunity to react with cellulose hydroxyl groups. Ekman et al [16] reported the use of liquid ammonia to increase the accessibility of cellulose hydroxyls groups for reaction with the reagent.…”
Section: Ammonium Hydroxide Neutralized Mso Reactionsmentioning
confidence: 99%